PENGARUH IKLAN SMARTPHONE TERHADAP PERILAKU BRAND SWITCHING KONSUMEN BAYUNG LENCIR MUSI BANYUASIN - Ade Nia Suryani (Jurnal Manajemen Kompeten, 2018)
This study aims to determine the effect of smartphone advertisements on consumer switching brand behavior in Bayung Lencir Subdistrict, Musi Banyuasin Regency. This research is a study of causality. The population of this study is consumers in the District of Bayung Lencir, especially those who use smartphones. The total sample of 100 people was determined using the Malhotra formula. The sample was selected using a purposive sampling technique. Data were collected using the questionnaire method and analyzed using simple linear regression analysis and correlation analysis. The results showed that (1) the correlation coefficient value of 0.844 showed that there was a very strong relationship or correlation between smartphone advertisements and consumer switching brand behavior in Bayung Lencir Subdistrict, Musi Banyuasin Regency, while the Adjusted R Square value of 0.709 indicated that smartphone advertising affected behavior consumer brand switching is 70.9%, (2) the results of the t hypothesis test show that smartphone advertising significantly influences the brand switching behavior of consumers in the Bayung Lencir District of Musi Banyuasin Regency with a tcount> ttable (15,576> 1,984).